(untitled) (Journal of the College of Education for Women, 2022)
The current research aims to examine the effect of the rapid learning method in developing creative thinking among second-grade female students in the subject of history. Thus, the researcher has adopted an experimental design of two groups to suit the nature of the research. The sample of the study consists of (36) randomly selected students from Al-Shafaq Secondary School for Women, which are divided randomly into two groups. The first group represents the experimental; it includes (31) students who studied the subject of history using the quick learning method. The second group, on the other hand, is the control group, which consists of (32) students, who studied the same subject using the traditional way. Before starting with the experiment, the researcher was keen to ensure that the students of the two research groups are statistically equal in a number of variables that are believed to have an effect on the safety of the experiment. Such variables involve: (the chronological age of the students calculated in months, intelligence, a pre-test for creative thinking, the academic level of the parents). To achieve the objective of the study, the researcher must use Tor Anas’ test that was Arabized by Sayed Khairallah to measure the creative thinking, and employ it for the contents of the Arab-Islamic history book. Accordingly, the researcher constructed (10) testing items for each of the following skills (fluency, flexibility, originality, and sensitivity to problems) to have a total of (40) items. Moreover, the performance of the students has been evaluated by identifying and treating their weak points to improve their level of knowledge, meeting as a result the already set objective and employing the students’ mental energies in creating a motivating atmosphere for creative thinking. The study has finally concluded that the quick learning strategy requires more effort and skill on the part of the teacher than when using the usual methods of teaching. It has further made the students more motivated, more willing to participate in the history lessons, and this has thus developed their creative thinking.